Changes in the Content of Pediatric Physical Therapy for Infants: A Quantitative, Observational Study. (20th October 2018) - Hielkema, Tjitske; Toonen, Rivka F.; Hooijsma, Siebrigje J.; Dirks, Tineke; Reinders-Messelink, Heleen A.; Maathuis, Carel G. B.; Geertzen, Jan H. B.; Hadders-Algra, Mijna
ABSTRACT: Aims : The aim of our observational longitudinal study is to evaluate changes over time in standard pediatric physical therapy (PPT) for infants at risk of neurodevelopmental disorders. Methods : Treatment sessions in two time periods (2003–2005 [ n = 22] and 2008–2014 [ n = 16]) were video recorded and analyzed quantitatively in five categories: neuromotor actions, educational actions, communication, position, and situation of treatment session. Differences in percentages of time spent on therapeutic actions between periods were tested with Mann–Whitney U and Hodges Lehmann's tests. Results : No significant changes appeared in the main categories of neuromotor actions. Time spent on not-specified educational actions toward caregivers (median from 99% to 81%, p = .042) and not-specified communication (median from 72% to 52%, p = .002) decreased. Consequently, time spent on specific educational actions (caregiver training and coaching; median from 1% to 19%, p = .042) and specific communication (information exchange, instruct, provide feedback; median from 21% to 38%, p = .007) increased. Infant position changed only minimally: time spent on transitions—that is, change of position—decreased slightly over time (median from 7% to 6%, p = .042). Situation of treatment session did not change significantly over time. Conclusions : Neuromotor actions in PPT remained largely stable over time. Specific educational actions and communication increased, indicating larger family involvement during treatment sessions.